Aurantimicrobium photophilum sp. nov., a non-photosynthetic bacterium adjusting its metabolism to the diurnal light cycle and reclassification of Cryobacterium mesophilum as Terrimesophilobacter mesophilus gen. nov., comb. nov. Issue 8 (25th August 2021) - Hahn, Martin W.; Pitt, Alexandra; Koll, Ulrike; Schmidt, Johanna; Maresca, Julia A.; Neumann-Schaal, Meina
Abstract : The aerobic primarily chemoorganotrophic actinobacterial strain MWH-Mo1 T was isolated from a freshwater lake and is characterized by small cell lengths of less than 1 µm, small cell volumes of 0.05–0.06 µm 3 (ultramicrobacterium), a small genome size of 1.75 Mbp and, at least for an actinobacterium, a low DNA G+C content of 54.6 mol%. Phylogenetic analyses based on concatenated amino acid sequences of 116 housekeeping genes suggested the type strain of Aurantimicrobium minutum affiliated with the family Microbacteriaceae as its closest described relative. Strain MWH-Mo1 T shares with the type strain of that species a 16S rRNA gene sequence similarity of 99.6 % but the genomes of the two strains share an average nucleotide identity of only 79.3 %. Strain MWH-Mo1 T is in many genomic, phenotypic and chemotaxonomic characteristics quite similar to the type strain of A. minutum . Previous intensive investigations revealed two unusual traits of strain MWH-Mo1 T . Although the strain is not known to be phototrophic, the metabolism is adjusted to the diurnal light cycle by up- and down-regulation of genes in light and darkness. This results in faster growth in the presence of light. Additionally, a cell size-independent protection against predation by bacterivorous flagellates, most likely mediated by a proteinaceous cell surface structure, was demonstrated. For the previously intensively investigated aerobic chemoorganotrophic actinobacterial strain MWH-Mo1 T (=CCUG 56426 T =DSM 107758 T ), the establishment of the new species Aurantimicrobium photophilum sp. nov. is proposed.